2016
DOI: 10.7863/ultra.15.02050
|View full text |Cite
|
Sign up to set email alerts
|

Prenatally Diagnosed Cases of Binder Phenotype Complicated by Respiratory Distress in the Immediate Postnatal Period

Abstract: Binder phenotype, or maxillonasal dysostosis, is a distinctive pattern of facial development characterized by a short nose with a flat nasal bridge, an acute nasolabial angle, a short columella, a convex upper lip, and class III malocclusion. We report 3 cases of prenatally diagnosed Binder phenotype associated with perinatal respiratory impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Since Quarrell’s description, several case reports have described prenatal 2-D and 3-D US and MRI findings, as early as 21 weeks of gestation [6, 9, 1316]. Levaillant et al [6] in 2009 reported a series of eight fetuses with Binder profile detected with ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Quarrell’s description, several case reports have described prenatal 2-D and 3-D US and MRI findings, as early as 21 weeks of gestation [6, 9, 1316]. Levaillant et al [6] in 2009 reported a series of eight fetuses with Binder profile detected with ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty in newborn ventilation can also be caused by airway compression from laryngeal calcifications or by central hypoventilation from spine entrapment/cervical stenosis [2]. Respiratory distress can be mild or severe, even with patent nares, patent trachea and normal lungs, and can require tracheostomy [16]. One group of authors suggested an ear, nose and throat otolaryngologist at the delivery room might be useful to support airway control [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binder phenotype can reveal underlying skeletal disorders particularly affecting cartilaginous zones and especially epiphyseal stippling. Effectively, published data suggest that Binder phenotype is very rarely isolated and is associated with chondrodysplasia punctata …”
Section: Introductionmentioning
confidence: 99%
“…Lack of fluid in the anterior nasopharynx on MRI, visualization of fluid‐filled nostrils, and spinal stenosis were reported by these authors as being possible prenatal features for predicting respiratory distress . Blumenfeld et al published three cases of respiratory impairment in neonates with Binder phenotype, leading to more and more obstetricians recommending giving birth in level III maternity wards. The authors suggest that distress was caused by a narrowed upper airway obstruction in the maxillonasal passage .…”
Section: Introductionmentioning
confidence: 99%